Varietal difference in the correlation between leaf nitrogen content and photosynthesis in rice (Oryza sativa L.) plants is related to specific leaf weight - Xi LIU; Yong LI (Journal of Integrative Agriculture, 2016)
Increasing leaf photosynthesis per area (A) is of great importance to achieve yield further improvement. The aim of this study was to exploit varietal difference in A and its correlation with specific leaf weight (SLW). Twelve rice cultivars, including 6 indica and 6 japonica varieties, were pot-grown under two N treatments, low N (LN) and sufficient N (SN). Leaf photosynthesis and related parameters were measured at tillering stage. Compared with LN treatment, A, stomatal conductance (gs), mesophyll conductance (gm), leaf N content (Narea), and chlorophyll content were significantly improved under SN treatment, while SLW and photosynthetic N use efficiency (PNUE) were generally decreased. Varietal difference in A was positively related to both gs and gm, but not related to Narea. This resulted in a low PNUE in high Narea leaves. Varietal difference in PNUE was generally negatively related to SLW. Response of PNUE to N supply varied among different rice cultivars, and interestingly, the decrease in PNUE under SN was negatively related to the decrease in SLW. With a higher Narea, japonica rice cultivars did not show a higher A than indica rice cultivars because of possession of high-SLW leaves. Therefore, varietal difference in A was not related to Narea, and SLW can substantially interfere with the correlation between A and Narea. These findings may provide useful information for rice breeders to maximize A and PNUE, rather than over reliance on Narea as an indicator of photosynthetic performance.